Psikoedukasi Anti-Bullying: Strategi Penguatan Empati Untuk Meminimalisir Perundungan Di Lingkungan Remaja (Studi Kasus SDN Cipeucang 02). - Aulia Zahrah; Erni Fitriani; Nurul Holisoh; Asti Sutriani; Eka Susanti (Annusfy : Journal of Multidisciplinary Research, 2026)
Bullying is a complex behavioral anomaly commonly found in the transitional phase of adolescent development, which risks degrading psychological stability and the educational atmosphere in educational environments. This community service initiative focuses on the application of anti-bullying psychoeducation as an instrument to strengthen the empathy capacity of 6th grade students at SDN Cipeucang 02. Through an experiential learning approach, this activity integrates participatory socialization, group dialogue, and prosocial behavior modeling. The program involved 120 students as subjects who were equipped with a comprehensive understanding of the categorization of bullying, whether physical, verbal, or relational. The outcome of this activity indicates an escalation of affective awareness, where participants are able to analyze the negative consequences of bullying and demonstrate strengthened empathy through simulation activities. Overall, this program facilitates the creation of a collective consensus to build a conducive school environment as a preventive measure in mitigating violence in early adolescence.